Epilepsy as a risk factor for hepatic encephalopathy in patients with cirrhosis: a cohort study - Jepsen, Peter (BMC Gastroenterol, 2016)
BACKGROUND: Epilepsy is associated with an increased mortality among cirrhosis patients, but the reasons are unknown. We aimed to determine whether epilepsy is a risk factor for developing hepatic encephalopathy (HE), which is a strong predictor of mortality. METHODS: We used data from three randomized 1-year trials of satavaptan in cirrhosis patients with ascites. With Cox regression, we compared the hazard rates of HE grade 1–4 between those cirrhosis patients who did or did not have epilepsy. We adjusted for confounding by gender, age, cirrhosis etiology, diabetes, history of HE, Model for Endstage Liver Disease (MELD) score, serum sodium, albumin, lactulose use, rifaximin use, and benzodiazepine/barbiturate sedation. In a supplementary analysis we examined the association between epilepsy and the hazard rate of HE grade 2–4. RESULTS: Of the 1120 cirrhosis patients with ascites, 21 (1.9 %) were diagnosed with epilepsy. These patients had better liver function at inclusion than the patients without epilepsy (median MELD score 7.9 vs. 11.4), and only one died during the trials. Nevertheless, seven patients with epilepsy had an HE episode during the follow-up, and the adjusted hazard ratio of HE grade 1–4 for patients with epilepsy vs. controls was 2.12 (95 % CI 0.99–4.55). The corresponding hazard ratio of HE grade 2–4 was 3.83 (95 % CI 1.65–8.87). CONCLUSIONS: Our findings suggest that epilepsy is associated with an increased risk of HE in patients with cirrhosis.